2006
DOI: 10.1038/sj.bjc.6603336
|View full text |Cite
|
Sign up to set email alerts
|

Randomised study of adjuvant chemotherapy for completely resected p-stage I–IIIA non-small cell lung cancer

Abstract: We evaluated the therapeutic usefulness of adjuvant chemotherapy in patients with completely resected non-small cell lung cancer (NSCLC). We also examined the relation between DNA ploidy pattern and the response to chemotherapy. A total of 267 patients with NSCLC (pathologically documented stage I, II, or IIIA) underwent complete resection, and DNA ploidy pattern was analysed. Patients with stage I disease (n ¼ 172) were randomly assigned to receive surgery alone (group A) or surgery followed by adjuvant chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Such models would also have to allow testing of drugs within a short time frame (6-8 weeks) to conform with timely initiation of therapy (25)(26)(27). The first generation xenografts of primary NSCLCs used in the present study were shown to fulfill these criteria.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Such models would also have to allow testing of drugs within a short time frame (6-8 weeks) to conform with timely initiation of therapy (25)(26)(27). The first generation xenografts of primary NSCLCs used in the present study were shown to fulfill these criteria.…”
Section: Discussionmentioning
confidence: 92%
“…The subrenal capsule graft site permits high tissue perfusion and hence promotes viability and growth of the xenografts and their retention of major histopathologic and genetic characteristics of the original cancers, making them useful for drug response evaluation (22)(23)(24). In the clinic, NSCLC patients in general receive adjuvant chemotherapy 3 to 6 weeks after surgery (25)(26)(27). In view of this, the determination of drug response must be completed within this time frame.…”
mentioning
confidence: 99%
“…Nine RCTs of postoperative adjuvant chemotherapy with UFT alone (Table 1A) [7][8][9][27][28][29] or UFT following CDDP-based regimen (Table 1B) 7,9,[30][31][32] have been reported. The 2nd study conducted by the West Japan Study Group for Lung Cancer Surgery (WJSG) is the landmark trial showing the effi cacy of postoperative adjuvant chemotherapy for resected NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…NAKAGAWA et al [59] found male sex to be associated with poorer OS (HR It is frequently observed that expression of biomarkers may vary between histological subtypes [14,15,18,22,23,25,26,51], which is another reason that the prognostic and predictive potential may vary depending on the frequencies of various histological subtypes in the study populations. Some articles in this review included several histological subtypes, while other articles focused solely on one histological subtype (tables 1-4), which needs to be kept in mind when comparing different studies on the same biomarker.…”
Section: Patient Characteristicsmentioning
confidence: 99%